2021
DOI: 10.1111/pan.14377
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment and optimization strategies to reduce perioperative respiratory adverse events in pediatric anesthesia—Part 1 patient and surgical factors

Abstract: Perioperative respiratory adverse events are common in pediatric anesthesia but some can lead to life-threatening hypoxemia. 1,2 Three quarters of critical incidents and at least one third of perioperative cardiac arrests are initiated by or are linked to an adverse respiratory event. 1,3 They directly lead to almost one third of all unplanned intensive care unit admissions and half of all anesthesia-related malpractice claims for children. 4,5 Fortunately, most perioperative respiratory adverse events are eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
16
1
1
Order By: Relevance
“…Postoperative respiratory complications in children who are symptomatic with upper respiratory infections (URI) other than SARS-CoV-2 appear to be more common, ranging from 24-30% [19] , [20] , [21] , [22] . As COVID-19 is now an endemic problem, moving forward it may be prudent to develop policies where symptomatic patients are treated the same as symptomatic patients with other URIs.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative respiratory complications in children who are symptomatic with upper respiratory infections (URI) other than SARS-CoV-2 appear to be more common, ranging from 24-30% [19] , [20] , [21] , [22] . As COVID-19 is now an endemic problem, moving forward it may be prudent to develop policies where symptomatic patients are treated the same as symptomatic patients with other URIs.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent reports have suggested that the long-held wisdom that children with OSA have increased sensitivity to the respiratory depressive effect of opioids may be inaccurate. 60,61…”
Section: Perioperative Opioidsmentioning
confidence: 99%
“…Pulse oximetry monitoring and potentially other measures of ventilation should be employed in these patients or other higher risk situations. Of note, recent reports have suggested that the long‐held wisdom that children with OSA have increased sensitivity to the respiratory depressive effect of opioids may be inaccurate 60,61 …”
Section: Main Articlementioning
confidence: 99%
“…26 Previous studies have demonstrated pediatric-specific risk factors for adverse respiratory events under general anesthesia, including younger age, a history of reactive airway disease, prematurity, the presence of an upper respiratory tract infection, obesity, obstructive sleep apnea, and tobacco smoke exposure in the home. 27 These factors help risk stratify patients presenting for anesthesia, 28 and may impact anesthetic choices. Understanding the effect of the air quality index on the incidence of adverse respiratory events under general anesthesia could be an important factor to help further assess these patients.…”
Section: Editor's Perspectivementioning
confidence: 99%